Teaching excellence in applied universities: The student perspective - Liu, Siyan; Binti Abdullah, Doria (Research Journal in Advanced Humanities, 2025)
Applied universities, which focus on training high-level technical talents, lack information on how gender and academic achievement affect students’ perception of effective teaching to inform curriculum enhancement in China. Thus, this research aims to explore the influence of gender and academic performance on students’ perceptions of excellent teaching in a typical Chinese applied university. In the present study, data was collected through semi-structured interviews with 13 senior students at the applied university, and the response was analysed through thematic analysis. It has been revealed that female students are especially concerned with the relevancy and up-to-date information in the materials, which they perceive as the characteristic of professional teaching. On the other hand, while male students were discussing lesson contents and their structures, they emphasised lesson delivery. Furthermore, it has also demonstrated that intelligent students with higher academic achievements embrace the value of updated content and claim that their teachings should reflect intellectual competency, with the craze of the current industry relevancy. The harmonious incorporation of humour and motivational approaches to teaching enhances the learning process and learning outcomes. Therefore, teaching skills, professional knowledge, and concern for students are found to be appreciated by male and female students, irrespective of their performance levels. These understandings provide the need to come up with teaching-learning techniques that consider different education requirements in furthering the Relevance and outreach of Higher Education in responding to diverse Learner and industry needs.